The role of erythropoietin stimulating agents in anemic patients with heart failure: solved and unresolved questions - Palazzuoli A; Ruocco G; Pellegrini M; De Gori C; Del Castillo G; Giordano N; Nuti R (Dove Medical Press, 2014)
Alberto Palazzuoli, Gaetano Ruocco, Marco Pellegrini, Carmelo De Gori, Gabriele Del Castillo, Nicola Giordano, Ranuccio NutiDepartment of Internal Medicine and Metabolic Diseases, Cardiology Section, Le Scotte Hospital, University of Siena, Siena, ItalyAbstract: Anemia is a common finding in congestive heart failure (CHF) and is associated with an increased mortality and morbidity. Several conditions can cause depression of erythroid progenitor cells: reduction of iron absorption and reuptake, decreased bone marrow activity, reduced endogenous erythropoietin production, and chronic inflammatory state. Anemia’s etiology in CHF is complex and partially understood; it involves several systems including impaired hemodynamic condition, reduced kidney and bone perfusion, increased inflammatory activity, and neurohormonal overdrive. The use of erythropoiesis stimulating agents (ESAs) such as erythropoietin and its derivatives is recently debated; the last interventional trial seems to demonstrate a neutral or negative effect in the active arm with darbepoetin treatment. The current data is opposite to many single blind studies and previous meta-analysis showing an improvement in quality of life, New York Heart Association class, and exercise tolerance using ESA therapy. These contrasting data raise several concerns regarding the target of hemoglobin levels needing intervention, the exact anemia classification and categorization, and the standardization of hematocrit cutoffs. Some cardiac and systemic conditions (ie, hypertension, atrial fibrillation, prothrombotic status) may predispose to adverse events, and ESA administration should be avoided. To prevent the negative effects, high-dosage and chronic administration should be avoided. Clarification of these items could probably identify patients that may benefit from additional iron or ESA treatment. In this review, we discuss the interventional trials made in anemic heart failure patients, the underlying mechanism of anemia in CHF, and the potential role of ESA in this setting.Keywords: anemia, iron metabolism, heart failure